Post 2030-Agenda and the Role of Space The UN 2030 Goals and Their Further Evolution Beyond 2030 for Sustainable Development (Studies in Space Policy,, 2018)
This book provides a deep insight to which extent further improvement should be envisaged to ensure and improve the sustainable development beyond 2030 (the Sustainable Development Goals is a set of 17 global goals with 169 associated targets which the state community adopted in 2015). As the world, its environment, economy and society is getting more and more technical advanced, it is of high interest to analyze how space and its various applications can support this development. Once the Goals of the "2030 Agenda for Sustainable Development" will be achieved new challenges are waiting. The analysis takes into account a proactive use of artificial intelligence for the development based on space infrastructure. Another important aspect revolves around the economic development which asks for further analysis of the cryptocurrencies relationship with space applications and how to use space based cryptocurrencies for development. Environment-wise the challenges for a sustainable development on Earth i.e. water supply, but also in outer space are requested ensuring a sustainable exploration and exploitation of space and its orbital resources. The book also highlights possible contributions of the post-2030 space industry to global economic development based on satellite technology and the enlargement of the scope of application of satellite data in administration and Justice to ensure development of effective, accountable and transparent institutions at all levels to promote growth, stability and security and peace on global level.